The Communicational Skills of Future Music Teachers - Aukštkalnytė, Dėja (Acta Paedagogica Vilnensia, 2002)
One of the most important principle of Lithuanian school reform nowadays and principal improvement of teacher-pupil relations is fostering of optimal pedagogical communication of future teachers. The research object of the article were peculiarities and development of communication skills of future music teachers. The goal of the research was to reveal the level of communicational skills of future music teachers and to compare them with the same skills of working music teachers. To be competent music teacher today is not enough to know special methodology of teaching. All methods and knowledge are transmitted by positive interpersonal communication between teacher and pupils. Insufficient knowledge and skills to communicate lead to many problems in pedagogical activity. So every teacher of our days needs to cultivate personal communication competency. The best start to be prepared to communicate competently is Universities and Academy of Music. Scientists agree that communicational skills is one of the main aspects of communication competence. The problems and tendencies of fostering communication skills are fairly well revealed in the works of Lithuanian and foreign scientists of today. Their inquiry into the content of communication, describe the main principles of its realization, its inward and outward conditions when comparing the character of communication in educational process. The studies of psychological, sociological and pedagogical literature reveal the fact that perceptional, communicational and interactional skills have some kinds. The main kinds of communicational skills are to use appropriately verbal and nonverbal codes, to organize music activity on partnership basis, and to create a good atmosphere in the lesson. All these kinds are formed from manifestations of every skill and its empirical indexes. The skill to use verbal codes appropriately has five manifestations: to do a preparatory work when planning to speak with pupils, to understand the pupil, to ask, to persuade, and to evaluate the effectiveness of the talk. The skill to use nonverbal codes appropriately owns skills to use the voice qualities, to use facial, mimic, and to use pantomimic properly. The skill to organize music activity on partnership basis includes: to do the goals of the lesson interesting for pupils, to plan how to realize the goals of the lesson, to administer the activity of the pupils, and to evaluate the results of the lesson. The skill to create a good atmosphere in the lesson owns four manifestations: to make the first contact with pupils, to listen them, to stimulate the trust, and to make stronger the solidarity between pupils. In the investigation took part 134 students and 158 music teachers. The results of investigation shows that communicational skills of them are not high enough to be competent communicators in music lesson. The common level of communicational skills is only middle.
Keywords: Higher education; teacher education; pedagogical communication; communicational skills.